2019
DOI: 10.1080/17437199.2019.1669481
|View full text |Cite
|
Sign up to set email alerts
|

Social identification-building interventions to improve health: a systematic review and meta-analysis

Abstract: There is growing evidence that social identity processes play an important role in a range of health outcomes. However, we know little about the nature and effectiveness of interventions that build social identification with the aim of promoting health. In the present research, we systematically review and meta-analyze interventions that build social identification to enhance health and wellbeing. A total of 27 intervention studies were identified (N=2,230).Using random-effects meta-regression, results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(104 citation statements)
references
References 129 publications
(101 reference statements)
7
97
0
Order By: Relevance
“…Hence, in contrast to classic team‐building interventions that aim at increasing group identification (and as a “byproduct” increase individual identification of the group members), the G4H intervention directly addresses individual‐level processes of shared social identities. A recent meta‐analysis (Steffens et al, 2019) provides promising evidence for the effectiveness of G4H interventions in diverse clinical and non‐clinical contexts.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Hence, in contrast to classic team‐building interventions that aim at increasing group identification (and as a “byproduct” increase individual identification of the group members), the G4H intervention directly addresses individual‐level processes of shared social identities. A recent meta‐analysis (Steffens et al, 2019) provides promising evidence for the effectiveness of G4H interventions in diverse clinical and non‐clinical contexts.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The underlying reasoning is that team identification allows employees to feel supported by their colleagues, thereby contributing to their ability to cope with stress (Haslam et al, 2009). In fact, a systematic review with studies conducted in more diverse applied contexts (e.g., in a community, health/clinical, educational, or organizational setting) revealed that team identification-building interventions benefit a variety of health outcomes, ranging from reduced stress, depression, and anxiety to enhanced well-being as well as cognitive and physical health (Steffens et al, 2020). Similar results have been recently found in the sport setting, where formal leaders as well as peer leaders demonstrating identity leadership, were found to create a psychologically safe environment through which individuals' burnout is buffered, thereby enhancing their health (Fransen et al, 2020c).…”
Section: Aim 2: Is Team Identification the Missing Link?mentioning
confidence: 99%
“…Social identity approach, including social identity theory (Tajfel & Turner, 1979) and self‐categorization theory (Turner, Hogg, Oakes, Reicher, & Wetherell, 1987), points out that belonging to the group affects individuals' emotion, cognition and behaviour (Hornsey, 2008; Wakefield, Bowe, Kellezi, McNamara, & Stevenson, 2019). On the one hand, the social cure perspective, which is arisen out of the social identity approach, has revealed that group identity enhances personal health and well‐being (Haslam, Jetten, Cruwys, Dingle, & Haslam, 2018; Steffens et al, 2019), sleep quality by reducing loneliness and depression (Wakefield, Bowe, Kellezi, Butcher, & Groeger, 2019), and satisfaction with life (Greenaway et al, 2015; Haslam, Cruwys, Chang, Eckley, Buckingham, & Channon, 2020). Recent evidences suggest that group identity is the foundation of volunteers' motivation and experience of volunteering (Gray & Stevenson, 2019), and it can increase pro‐environmental behaviour (Fritsche, Barth, Jugert, Masson, & Reese, 2017).…”
Section: Introductionmentioning
confidence: 99%